Analisis Problematika Pembelajaran Pecahan Campuran serta Optimalisasi Game Kotak Pertanyaan Cerdas sebagai Solusi Pembelajaran pada Kajian Kapita Selekta Pendidikan Matematika SMP - Nur Hasanah; Fathor Rakhman (Academy of Education Journal, 2026)
This study aims to identify the challenges students face in learning mixed fraction multiplication and to implement a solution in the form of the Smart Question Box educational game for grade VII C students at SMP Negeri 3 Panji. The study used a mixed approach, beginning with qualitative data collection through classroom observations and teacher interviews to identify students' difficulties in understanding mixed fractions. Initial results indicated that students experienced difficulties converting mixed fractions, simplifying results, and carrying out arithmetic procedures regularly. Subsequently, the Smart Question Box solution was implemented in the learning process, and its effectiveness was measured quantitatively through a Likert-scale questionnaire completed by 25 students. The results showed that 46.8% of students strongly agreed and 46.8% agreed that the game helped improve their understanding, motivation, and engagement in learning, while 6.4% gave less positive responses. These findings confirm that the Smart Question Box is effective as an interactive learning medium for improving understanding of mixed fraction concepts, making it worthy of recommendation as an alternative learning strategy for similar material.